CHATBOTS IN PUBLIC SERVICE TRANSFORMATION: A SYSTEMATIC LITERATURE REVIEW OF E-GOVERNMENT - Nanda Risky Firmandany; Muhammad Raynar Hammam; Kinnaras Aryapoetra (Jurnal Riset Sistem Informasi, 2026)
This study presents a systematic literature review of 100 publications published between 2019 and 2025 to examine the development of chatbot research in e-government, focusing on research trends, methodologies, chatbot types, and application domains. The findings reveal a significant increase in the adoption of chatbots in public services, with task-oriented chatbots dominating applications such as information services, civil administration, taxation, and licensing. Experimental studies, surveys, and interviews are the most commonly employed research methods, indicating a strong emphasis on evaluating system effectiveness and user acceptance. Despite their potential to enhance service efficiency and accessibility, chatbot implementations face persistent challenges related to response accuracy, citizen trust, organizational readiness, and ethical as well as data governance issues. The review also identifies an emerging shift toward the use of generative AI to support more natural and adaptive interactions in public services. This study contributes by providing a comprehensive and up-to-date synthesis of chatbot research in e-government, highlighting key challenges and research gaps that can inform future policy development, system design, and empirical studies in digital government.